Antibacterial Activity of Sweet Orange (Citrus sinensis) Peel Tea against Enterobacteriaceae Isolated from a Water Depot - Yumiko, Yumiko; Suhartomi, Suhartomi; Nasution, Sri Wahyuni; Syarifah, Siti; Simaremare, Ade Pryta R. (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Most orange peels are not utilized and become useless waste that is thrown away. Orange peels contain many nutrients and compounds, such as flavonoids, terpenoids, alkaloids, and essential oils, which are secondary metabolites that act as antibacterial agents. This study intends to investigate the antibacterial activity of sweet orange peel tea against isolated Enterobacteriaceae from a random water depot sample around Universitas Prima Indonesia. This experiment used disc diffusion for antibacterial assay. Meanwhile, the sweet orange peel was brewed using two different methods, including infusion and decoction, in two different masses (3 grams and 5 grams). These sweet orange peel tea formulations were compared to standard (chloramphenicol) and control (distilled water). Enterobacteriaceae was isolated and identified from a random water depot sample around Universitas Prima Indonesia, which included colony identification in EMB agar and MacConkey agar, gram staining, and biochemical test. This study showed that a random water depot sample contaminated by Enterobacteriaceae had properties similar to Citrobacter sp. Sweet orange tea formulation inhibited this isolated Enterobacteriaceae growth (P-Value: 0.010). Antibacterial activity was observed in 3-gram infusion, 5-gram infusion, and 5-gram decoction. However, the antibacterial activity was not better than the standard (chloramphenicol). Overall, it can be concluded that the sweet orange peel tea as infusion or decoction has weak antibacterial activity against Enterobacteriaceae bacteria isolated from water depots, which had some properties similar to Citrobacter sp.